2007
DOI: 10.1007/s10162-007-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Hearing Loss in C57BL/6J Mice has both Frequency-Specific and Non-Frequency-Specific Components that Produce a Hyperacusis-Like Exaggeration of the Acoustic Startle Reflex

Abstract: Auditory brainstem-evoked response (ABR) thresholds were obtained in a longitudinal study of C57BL/6J mice between 10 and 53 weeks old, with repeated testing every 2 weeks. On alternate weeks, acoustic startle reflex (ASR) amplitudes were measured, elicited by tone pips with stimulus frequencies of 3, 6, 12, and 24 kHz, and intensities from subthreshold up to 110 dB sound pressure level. The increase in ABR thresholds for 3 and 6 kHz test stimuli followed a linear time course with increasing age from 10 to 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
126
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 36 publications
16
126
2
Order By: Relevance
“…Linear regressions (implemented in MATLAB using the regress function) found statistically significant correlations (PG0.05) between relative ASR and 8-kHz thresholds at lead times of 1 and 2 ms. As previously noted (Ison et al 2007), these results suggest that the exaggerated ASR at short lead times is a manifestation of a hyperacusis-like phenomenon in mice with hearing loss. Despite the statistical significance of this relationship, affected mice in the present study showed modest threshold shifts (∼10 dB) relative to FIG.…”
Section: Effect Of Rearing Environment On Abr Thresholdssupporting
confidence: 86%
See 1 more Smart Citation
“…Linear regressions (implemented in MATLAB using the regress function) found statistically significant correlations (PG0.05) between relative ASR and 8-kHz thresholds at lead times of 1 and 2 ms. As previously noted (Ison et al 2007), these results suggest that the exaggerated ASR at short lead times is a manifestation of a hyperacusis-like phenomenon in mice with hearing loss. Despite the statistical significance of this relationship, affected mice in the present study showed modest threshold shifts (∼10 dB) relative to FIG.…”
Section: Effect Of Rearing Environment On Abr Thresholdssupporting
confidence: 86%
“…3B) was the potentiated startle response at a lead time of 1 ms. This exaggeration of the startle response has been previously described in older C57BL/6 J mice (Ison et al 2007). Because the effect came at a later age relative to the age-related loss of cochlear hair cells, it has been attributed to a reorganization of the central afferent pathways that follows the disruption of peripheral inputs.…”
Section: Effect Of Rearing Environment On Giasrsupporting
confidence: 54%
“…CBA/J mice are known for their persistent hearing sensitivity while C57BL/6J mice suffer from an early onset of high-frequency hearing loss so far reported to start at 2 months of age (Mikaelian, 1979;Henry and Chole, 1980;Li and Borg, 1991;Henry, 2004;Ison et al, 2007) The present data suggest that the deterioration of hearing sensitivity in C57BL/6J mice might even begin at the end of the first postnatal month. Except for threshold values, we did not find any major indications for strain-specific differences in spontaneous and acoustically evoked discharge characteristics of MNTB units.…”
Section: Sound-evoked Discharge Propertiesmentioning
confidence: 51%
“…These two methods have already been described in detail in the literature. As generally accepted, the magnitude and peak latency of the SR response are the basic parameters of this method [10,11] . In this study, SRT was used to determine the subjective auditory threshold of the mice, and GDT was employed to detect tinnitus induction.…”
Section: Discussionmentioning
confidence: 99%